The Merging of Gojek and Tokopedia Forms Go To. Is This a Threat to National Banking and Fintech? - Harimurti, Cundo; Sofyan, Mohammad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This research aims to examine various literature which is used synthetically to explain the phenomenon of the merger of Gojek and Tokopedia into GoTo which is predicted to be a challenge for national banks and fintech in lending. The research results show that Banking and fintech have different characteristics but target the same market niche. Fintech has disrupted various economic activities, including the financial sector. The role of fintech, which is quite large and very flexible, needs to be addressed as an enabler, not as a competitor in the financial sector. So, the financial sector needs to collaborate with fintech in providing financial services or creating new products for consumers.